Penerapan pengolahan telur itik dengan oven pengasapan pada UKM petani sawit di Kampung Sialang Baru, Kabupaten Siak, Riau - Yusfiati Yusfiati; Rr. Sri Catur S; Siti Fatonah; M. Yulis Hamidy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The duck farming business can develop well by improving the management of duck eggs into smoked salted eggs of various flavors. The service activity aims to educate members of the Sialang Baru Palm Oil Farmers UKM about the use of cadling and processing smoked salted eggs with various flavors. The target community for this activity is around 15 people. The service method has three stages, namely first, making leaflets about candling and making smoked salted eggs. Second, the provision of material through socialization activities, in the form of lectures and discussions. Third, the practice of using egg candling and the practice of processing smoked salted eggs of various flavors. Evaluation by giving questionnaires before and after the lecture to participants. The results of the questionnaire were tabulated and described. The results of the dedication resulted in making salted eggs by smoking better than ordinary salted eggs. The taste of the egg texture is better and the yolk color is more yellow than ordinary salted eggs. Shorter manufacturing time is 7 days and smoking is 12 hours. The use of a smoked oven from a used drum is designed to have 3 shelves for eggs and fuel with wood husks. The people of the Sialang Baru Palm Oil UKM were very enthusiastic with the attendance of more than 70%. The counseling and practice of processing smoked salted eggs have educated the community to further develop their business in the future.